An Autopsy Study of Cases of Death Due to Poisoning - Aisha Rasheed, Usman Shahid Butt, Noreen Farid, Ijaz Aziz, Hafiza Naima Anwar, Perwaiz Ahmed Makhdoom (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To describe the socio-demographic profile of deaths due to poisoning and to assess frequency of poisoning deaths, among the autopsies Design of the Study: Descriptive cross sectional study. Study Settings: The study was conducted at Department of Forensic Medicine and Toxicology Liaquat University of Medical and Health Sciences Jamshoro Sindh from January 2021 to December 2021. Material and Methods: The present study was carried out in the Department of Forensic Medicine from. During this period, 313 autopsies were conducted, out of which, majority of cases were poisoning deaths. Among them 100 cases of Poisoning deaths were selected for the study based on purposive sampling and Chemical Analysis Report. Results of the Study: The most common poisons encountered in this study were OP compound (55 - 50%) and Phosphide ions (33 - 30%). Congestion (24 – 21.81%) and pulmonary edema (19 – 17.27%) was the most common findings in the lungs in cases of OP compound poisoning; whereas, pulmonary hemorrhage (12– 10.90%) and congestion (11– 10%) was the most common findings in the lungs in cases of Phosphide ion poisoning. Necrosis (16– 14.54%) and sinusoidal dilatation (14– 12.72%) was the most common findings in the liver in cases of OP compound poisoning; whereas, necrosis (21– 19.09%) and fatty change (09 – 8.18%) were the most common findings in the liver in cases of Phosphide ion poisoning. Conclusion: The most common form of poison taken by this research cases is organophosphorus pesticides. Males are more likely to be poisoned than females. In both rural and urban communities, married people outnumbered single people. Based on the information provided by the police and families of the deceased, the suspected type of poison in the majority of the victims remained unclear prior to autopsy.